Coastal Engineering Journal - Coastal Engineering Journal (Taylor & Francis, 2026)
Coastal Engineering Journal is a peer-reviewed medium for the publication of research achievements and engineering practices in the fields of coastal, harbor and offshore engineering. The CEJ editors welcome original papers and comprehensive reviews on waves and currents, sediment motion and morphodynamics, as well as on structures and facilities. Reports on conceptual developments and predictive methods of environmental processes are also published. Topics also include hard and soft technologies related to coastal zone development, shore protection, and prevention or mitigation of coastal disasters. The journal is intended to cover not only fundamental studies on analytical models, numerical computation and laboratory experiments, but also results of field measurements and case studies of real projects.
FI 0.52
Q2
Keywords: Engineering; Computing & Technology; Ingeniería costera; Acuerdos transformativos; Transformative agreements; Ingeniería portuaria; Ingeniería marina; Morfodinámica